RESPON PERTUMBUHAN JELUTUNG RAWA (Dyera polyphylla (Miq).V. Steenis.) TERHADAP PUPUK NPK PADA LAHAN GAMBUT (Respons of Jelutung (Dyera polyphylla (Miq).V. Steenis.) toward NPK Manure on the Peat Land): Christopheros, Gimson Luhan, V.S.G. Nyahu dan Johansyah - Admin JHT (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2018)
ABSTRACTThe National Movement for Forest and Land Rehabilitation Program (GNRHL orGerhan) proclaimed in 2003, it is advisable to plant timber species, superior plantspecies, endemic plants and multipurpose species. Jelutung swamp (Dyera polyphyllaMiq. Steenis.) Is one of the types that fulfill the criteria, so it is promoted as a type offorest and peatland rehabilitation. The basic consideration of swamp jelutung has a goodadaptability and is tested on peatlands, its growth is relatively fast and can be cultivatedwith minimal land manipulation, and can be obtained the result of double result that iswood and sap. Peat soils have relatively low productivity due to poor nutrients, so needto pay attention to the nutrient needs of the plants. The solution needs to be donefertilization, you should use a complete fertilizer type such as NPK. Selection of NPKMutiara fertilizer because it includes inorganic fertilizer that has the advantage that is, theprovision of fertilizer can be measured and the dosage is right. The objective of thisresearch is to know how to fertilize and dose of NPK Mutiara fertilizer which givesoptimum growth on swamp jelutung plant. The expected benefits are as materialinformation and consideration of the selection of species for reforestation andrehabilitation of peatlands that want to develop the type of jelutung swamp plants.Keywords: plant growth, NPK, peat, jelutung swamp.